Spirit and self: a holistic approach to Afro-Caribbean Canadian youth mental health care - Edwards, Fiona (My University, 2025)
Black youth continually experience stressful environmental conditions that negatively impact their mental health and well-being. Some seek religious and spiritual support to cope with these daily environmental stressors. Although the practice of spirituality through religious activities has allowed Black people and their communities to find meaning and comfort during times of pain, cope with injustices, and find hope for a better tomorrow, most of what is known about the importance of religiosity and spirituality in Black communities originates from research conducted in the United States. Within the Canadian context, the religious and spiritual experiences of Black youth, especially those of Afro-Caribbean background, are rare within the field of social work education and practice. This article presents data from six Afro-Caribbean Canadian youth (ACCY) between the ages of 16 and 18, two parents, and three faith-based leaders drawn from a doctoral youth-centered phenomenological study in Canada. By sharing their perspectives, this article examines the impacts of religious and spiritual support on the lives of ACCY. Recommendations for the use of religiosity and spirituality in social work education and practice are discussed.
Keywords: Afro-Caribbean Canadian youth; religiosity/spirituality; anti-Black racism; mental health; social work education and practice